PERBUATAN MELANGGAR HUKUM OLEH MASKAPAI PENERBANGAN TERKAIT PEMBATALAN DAN KETERLAMBATAN PENGANGKUTAN - Bayu Mahardika, Ida Bagus; Sandhi Sudarsana, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 01, Februari 2014)
This paper tittled “Onrechtmatige daad by Airlines Company Related to The Cancellation and The Delay of Transport”. In this paper, it is used normative methode which try to resolve the problem’s rooted by the literature and statutes.The problem of delay and cancellation often we experience in the world of airlines. It is definitely suffering the kind of loss for the passanger. Whether is the problem of cancellation and the delay included the Onrechtmatige daad, it will be explain further in this paper.
Keywords: Company, Onrechtmatige daad, Cancellation, Delay